Removal of Misplaced Intramedullary Nails for Proximal Phalanx and Metacarpal Fixation - Nirbhay S. Jain, MD; Teun Teunis, MD, PhD (Journal of Hand Surgery Global Online)
Intramedullary nails for finger and metacarpal fracture fixation are gaining popularity. Given the increased usage, the number of adverse events will increase proportionally. In our practice, we have encountered several instances where we had to remove a previously placed intramedullary nail, for which there is no standard approach. This article describes our experience with removing intramedullary nails to benefit surgeons encountering similar situations.